Synthesis and Characterization of ZnO@SiO₂ Composite for Microwave Absorber Applications - Fauzan, Muhammad; Bakti, Aditia Nur; Trivida, Elvina; Dewi, Nova Nur Elisa; Triyono, Djoko; Sugihartono, Iwan (Journal of the Physical Society of Indonesia, 2025)
This study aims to synthesize ZnO@SiO₂ composites via biosynthesis using Moringa oleifera leaf extract and to investigate the effect of different SiO₂ contents (pure ZnO, 1%, 3%, and 5% by weight) on their structural and microwave absorption properties, with ZnO prepared from a Zn(NO₃)₂·4H₂O precursor and calcined at 450 °C for 2 hours. The synthesized samples were characterized using X-ray Diffraction (XRD) and a Vector Network Analyzer (VNA). XRD results confirmed that all samples exhibited a hexagonal wurtzite crystal structure with space group P6₃mc and showed no secondary phases. The crystallite size decreased with increasing SiO₂ content, indicating nanoparticle formation and reduced crystallinity. VNA measurements showed that the ZnO@SiO₂ sample with 3% SiO₂ exhibited the best microwave absorption performance, with a minimum reflection loss (RL) value of –2.0251 dB at a frequency of 6.125 GHz. These results suggest that the 3% composition achieved better impedance matching and enhanced absorption efficiency.